The European Federation of the Pharmaceutical Industry and Associations' Research and Animal Welfare Group: Assessing and benchmarking 'Culture of Care' in the context of using animals for scientific purpose. (October 2020) - Robinson, Sally; Sparrow, Sue; Williams, Bella; Decelle, Thierry; Bertelsen, Thomas; Reid, Kirsty; Chlebus, Magda
The European Federation of Pharmaceutical Industries and Associations' Research and Animal Welfare group members reflected on the concept of a Culture of Care in relation to animal care and use and on differences in its understanding and application across European pharmaceutical companies. The term 'Culture of Care' is used across different regions and organizations but rarely with any defined indicators to support working practice. The European Federation of Pharmaceutical Industries and Associations' Research and Animal Welfare group has developed a framework to help organizations identify gaps or potential areas for improvement in support of a positive Culture of Care. The framework is a tool that identifies five areas of focus for a Culture of Care: company values; strategic approach at establishment level; implementation structures; staff support; and animal care and procedures. The framework is intended as an aid for continuous improvement, highlighting where indicators of good practice are present. We expect it to provide points of reflection and ideas for those looking to implement a Culture of Care in a structured way, while facilitating a professional and strategic approach. To prevent it supporting a 'tick-box' exercise, the framework must not be used as an auditing tool, but as a starting point for consideration and discussion about how care manifests within the context and constraints of individual establishments.